2015
DOI: 10.3389/fnagi.2015.00011
|View full text |Cite
|
Sign up to set email alerts
|

Expressive suppression and enhancement during music-elicited emotions in younger and older adults

Abstract: When presented with emotional visual scenes, older adults have been found to be equally capable to regulate emotion expression as younger adults, corroborating the view that emotion regulation skills are maintained or even improved in later adulthood. However, the possibility that gaze direction might help achieve an emotion control goal has not been taken into account, raising the question whether the effortful processing of expressive regulation is really spared from the general age-related decline. Since it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 71 publications
4
23
2
Order By: Relevance
“…Young and older adults experience increased SCLs when asked to suppress their expressivity in response to a sad film (Lohani & Isaacowitz, 2014). Other studies have found decreased SCLs among both age groups when asked to suppress negative emotion in response to negative music (Vieillard, Harm & Bigand, 2015) and disgusting films (Kunzmann, Kupperbusch & Levenson, 2005) with the former showing some evidence that older adults experience a longer lasting decrease in SCL.…”
Section: Age-related Differences In Emotion Regulationmentioning
confidence: 84%
See 3 more Smart Citations
“…Young and older adults experience increased SCLs when asked to suppress their expressivity in response to a sad film (Lohani & Isaacowitz, 2014). Other studies have found decreased SCLs among both age groups when asked to suppress negative emotion in response to negative music (Vieillard, Harm & Bigand, 2015) and disgusting films (Kunzmann, Kupperbusch & Levenson, 2005) with the former showing some evidence that older adults experience a longer lasting decrease in SCL.…”
Section: Age-related Differences In Emotion Regulationmentioning
confidence: 84%
“…All studies assessing behavioral outcomes using facial EMG have found that both young and older adults are equally able to reduce their facial reactivity when instructed to suppress their expression of emotion. This has been demonstrated in response to positive and negative music (Vieillard, Harm & Bigand, 2015), sad films (Lohani & Isaacowitz, 2014), and negative images (Pedder et al, 2016). However, physiological data shows that suppression of negative emotion in response to music results in higher systolic blood pressure among older, but not younger adults (Vieillard, Harm & Bigand, 2015).…”
Section: Age-related Differences In Emotion Regulationmentioning
confidence: 96%
See 2 more Smart Citations
“…• sensitivity to sad and scary music drops [21,22]; scary music is assessed more positively; sad music is perceived as less sad [23]; negative music causes less emotional tension [24];…”
Section: Model Of Measuring Emotions As the Means For Researching Thementioning
confidence: 99%